2018
DOI: 10.1007/s11605-017-3627-3
|View full text |Cite
|
Sign up to set email alerts
|

18-Fluorodeoxyglucose Positron Emission Tomography Predicts Recurrence in Resected Pancreatic Ductal Adenocarcinoma

Abstract: Surgical resection failed to achieve CA19-9 normalization in the high PET group and distant recurrence was frequent. This suggests the potential for residual cancer at distant sites, even after curative resection. Stronger preoperative systemic chemotherapy is preferred for the high PET group patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Our results confirm previous evidence [ 22 , 23 , 37 , 38 , 39 , 40 , 41 , 42 ] of SUVmax (measured in terms of the tumor’s uptake of 18-FDG) being a simple and reliable pretreatment prognostic parameter, as in other malignancies. A summary of the results of other studies on SUVmax as a prognostic factor in cases of resectable pancreatic cancer is given in Table 4 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results confirm previous evidence [ 22 , 23 , 37 , 38 , 39 , 40 , 41 , 42 ] of SUVmax (measured in terms of the tumor’s uptake of 18-FDG) being a simple and reliable pretreatment prognostic parameter, as in other malignancies. A summary of the results of other studies on SUVmax as a prognostic factor in cases of resectable pancreatic cancer is given in Table 4 .…”
Section: Discussionsupporting
confidence: 91%
“…Including ours, seven studies have been published [ 22 , 23 , 38 , 39 , 40 , 41 ], all retrospective, concerning a total of 658 patients. SUVmax cut-offs vary greatly, but all the studies report a significantly longer DFS for patients with a low SUVmax, and 4 studies also describe a significantly better OS [ 23 , 38 , 40 , 41 ]. Since SUVmax only gives an indication of peak metabolic activity, not of tumor burden, some authors have explored the value of metabolic tumor volume (MTV) and total lesion glycolysis (TLG) as predictors of pancreatic cancer outcome [ 40 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…After removal of 690 duplicates, a further 2588 articles were excluded after title and abstract screening because they did not meet the prespecified inclusion criteria. The full texts of the remaining 468 studies were evaluated in more detail, and 89 studies were found to meet the eligibility criteria for this systematic review. Among them, 22 studies containing information on clinical factors relevant to recurrence sites were selected for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane Collaboration tool for assessing risk of bias showed that one study had no domain with a high risk of bias and three studies had one of seven domains with a high risk of bias ( Table S3 , supporting information). The overall risk of bias in non‐randomized studies, according to ROBINS‐I, was moderate in 48 studies and serious in 37 studies ( Table S4 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, identifying particular tumor characteristics associated with poor prognosis is important at the initial assessment. Numerous 18F-fluorodeoxyglucose (FDG)-PET reports have demonstrated the efficacy of conventional PET features such as maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) for predicting therapeutic response and prognosis [6][7][8][9] . However, those conventional PET features do not represent the spatial tumoral heterogeneity, which is deeply associated with cellular and molecular characteristics such as cellular proliferation and necrosis 10,11 .…”
mentioning
confidence: 99%